Inflectional Affixes In Book #88 Love Life 03 - Ni Luh Ayu Shinta Andriani; Ni Luh Sutjiati Beratha; Ni Wayan Sukarini (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This research explores the use of inflectional affixes in Book #88 Love Life 03 by Diana Rikasari, using Victoria Fromkin’s morphological framework. Inflectional affixes are suffixes added to words to express grammatical features such as tense, number, possession, aspect, and degree, without changing the word’s original class or core meaning. The purpose of this research is to identify and analyze the types and functions of these affixes within the selected text. The research used a qualitative method with a descriptive approach. Data was collected through documentation and analyzed using note-taking and cross-checking techniques to ensure accuracy. The results show that all eight standard English inflectional affixes were found in the book: -s (plural and third-person-singular), -ed (past-tense), -ing-(progressive), -en (past participle),--’s (possessive), -er (comparative), and -est (superlative). Each affix was used to mark specific grammatical functions and was essential in maintaining proper sentence structure. The analysis highlights that inflectional affixes play a key role in creating clear and grammatically correct sentences. Understanding their use helps readers and language learners grasp how meaning and structure are expressed in written English. This research supports the importance of morphological analysis in understanding how language functions at the word level and contributes to effective communication.